2016
DOI: 10.17116/terarkh201688778-83
|View full text |Cite
|
Sign up to set email alerts
|

Molecular serological characteristics of weak D antigen types of the Rhesus system

Abstract: The weak D antigen could be serologically identified in 96.8% of cases. When testing for weak D, particular attention should be given to people with the D-negative phenotype who had the C or E antigens. Our investigations conducted for the first time in Russia will be able to improve the immunological safety of red blood cell-containing medium transfusions for patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…Distribution of these alleles has been poorly studied so far. While RHD*weak D type 1.1 was initially thought to be restricted to a North‐Western area of Germany (Doescher et al, ), it was identified in Denmark and Russia (Christiansen et al, ; Golovkina et al, ), and more recently in 3/100 weak D samples in Australia (McGowan et al, ). These observations suggest that extended genotyping of the whole gene sequence may result in the identification of subtypes.…”
Section: Alleles and Genotyping Datamentioning
confidence: 99%
“…Distribution of these alleles has been poorly studied so far. While RHD*weak D type 1.1 was initially thought to be restricted to a North‐Western area of Germany (Doescher et al, ), it was identified in Denmark and Russia (Christiansen et al, ; Golovkina et al, ), and more recently in 3/100 weak D samples in Australia (McGowan et al, ). These observations suggest that extended genotyping of the whole gene sequence may result in the identification of subtypes.…”
Section: Alleles and Genotyping Datamentioning
confidence: 99%
“…В России молекулярно-генетические методы при иммуногематологических исследованиях используют редко. Публикации с описанием случаев диагностики данных вариантов антигена немногочисленны [2,3,[11][12][13].…”
Section: актуальностьunclassified